Removal of organic pollutants by contact oxidation of biological carbon sludge. (23rd June 2020) - Song, Wuchang; Ren, Yanglong; Jia, Ruibao; Zhao, Liang; Chen, Faming; Zhu, Zhaoliang
Abstract: A pilot‐scale (5 m 3 /day) study was conducted for the treatment of micro‐polluted low‐turbidity water using a biological contact oxidation high‐density sedimentation tank system with biochar sludge. First, the best operating conditions were found through system debugging; then, biological characteristics were investigated during system debugging; and finally, the performance in terms of pollutant elimination was investigated. The carbon sludge tank biomass was stable, which provided good stability for the removal of organic matter in raw water. The average reduction in absorbance of UV254 and total organic carbon were 36.71% and 29.63%, respectively, when compared with conventional coagulation. The adsorption and degradation of the mixture comprising carbon and sludge played an important role in removing organic pollutants; most of the humic and fulvic acid content of the water was removed during the coagulation processes. Practitioner points: The contact oxidation of biological carbon sludge system can effectively treat low‐turbidity water. The extracellular polymeric substances and the filamentous bacteria connecting the structure provided good settling for the carbon sludge mixture. The adsorption and degradation of the mixture comprising carbon and sludge played an important role in removing organic pollutants. With the carbon sludge reflux, organic matter with molecular weight >30K and 10K–3K was greatly reduced. The contact oxidation of biological carbon sludge system was successful in reducing the concentrations of DBPs and their precursors. Abstract : To solve the problem that the traditional pretreatment process such as coagulation has a poor effect on the treatment of the low‐turbidity micro‐polluted low‐turbidity water, a bio‐contact oxidation high‐density sedimentation tank system was built in this study. The average reduction in absorbance at UV254 and total organic carbon were 36.71% and 29.63%, respectively, compared with coagulation. The carbon sludge tank biomass can provide good stability for the removal of organic matter in raw water. The adsorption and degradation of the mixture comprising carbon and sludge played an important role in removing organic pollutants.